Infrastructure for development : a policy agenda for the Caribbean (IDB [Washington]US, 1996)
Seeks to identify the options for public sector modernization in selected countries in the Caribbean region with special reference to infrastructure, namely power, roads, airports, seaports, water and sanitation, and solid and hazardous wastes. Focuses on the Bahamas, Barbados, Belize, Dominica, Guyana, Jamaica, St. Kitts and Nevis, St. Lucia, Suriname and Trinidad and Tobago.
DC